1996
DOI: 10.1089/vim.1996.9.73
|View full text |Cite
|
Sign up to set email alerts
|

Anti-idiotypic Antibody to the V3 Domain of gp120 Binds to Vimentin: A Possible Role of Intermediate Filaments in the Early Steps of HIV-1 Infection Cycle

Abstract: Although the CD4 molecule is the major cellular receptor for human immunodeficiency virus (HIV), several lines of evidence suggest participation of additional molecules that are engaged after the binding of HIV to the CD4 receptor and that may facilitate viral entry into the target cell. Some of the post-CD4 binding, perfusion events involve the third hypervariable region (V3 loop) of the viral envelope protein gp120. To identify cellular proteins that interact with the V3 loop, we chose as a probe an antiidio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Our proteomic studies found specific luteal-phase-overexpressed proteins that might be involved in enhancing HIV-1 infection: moesin (39), cathepsin G (40, 41), myeloperoxidase isoform (42), an isoform of heterogeneous nuclear ribonucleoproteins C1/C2 (43), vimentin (44), and kallikreins (45,46). Interestingly, cathepsin G, a protease, is known to be inhibited by the follicular phase-overexpressed serpins (reviewed in reference 47), which alludes to a fine balance between proteases and antiproteases in the two menstrual phases, an aspect critical to the innate mucosal immune response.…”
Section: Discussionmentioning
confidence: 97%
“…Our proteomic studies found specific luteal-phase-overexpressed proteins that might be involved in enhancing HIV-1 infection: moesin (39), cathepsin G (40, 41), myeloperoxidase isoform (42), an isoform of heterogeneous nuclear ribonucleoproteins C1/C2 (43), vimentin (44), and kallikreins (45,46). Interestingly, cathepsin G, a protease, is known to be inhibited by the follicular phase-overexpressed serpins (reviewed in reference 47), which alludes to a fine balance between proteases and antiproteases in the two menstrual phases, an aspect critical to the innate mucosal immune response.…”
Section: Discussionmentioning
confidence: 97%
“…Although TFP/p6 pol lies outside (and upstream) of the protease, the EDL tripeptide of this cleavage site (ENL in the case of C viruses) has been postulated to have a major influence on protease activation and on the timing and specificity of GagPol cleavage, delaying the release of the protease until after the viral particle has budded from the cell membrane. Such a mechanism may protect the cell from the cytotoxic effects of proteolysis (36,38). The observed subtype variation in the cleavage sites controlling the initiation and rate of Gag and Gag-Pol processing (p2/NC) and the activation of protease (TFP/p6 gag ) suggests that there may be important differences in the way that B and C viruses regulate polyprocessing and virion assembly.…”
Section: Discussionmentioning
confidence: 99%
“…USA 93 (1996) 11861 like core but are composed exclusively of Gag (MA, CA, NC, and p6) and Env (gp4l and gp120) proteins (19). These pseudovirions package HIV-1 gag RNA and, as we have shown recently (26), translocate this RNA into the nucleus of an infected cell in a manner similar to the behavior of HIV-1 preintegration complexes. Results presented in Fig.…”
Section: Methodsmentioning
confidence: 75%
“…Beads were then pelleted by centrifugation and washed three times with PBS supplemented with 0.1% Tween 20, 1 ,ug/ml each of leupeptin and aprotinin, and 1 mM PMSF. HIV-1 DNA was isolated from the beads by SDS/proteinase K treatment with subsequent phenol-chloroform extraction, as described (22) (26). To control for possible differences in cell entry of wild-type versus mutant agents, HIV-specific nucleic acids were extracted directly from cytoplasmic extracts and assayed by RT-PCR (lanes 4 Proc.…”
Section: Methodsmentioning
confidence: 99%